ANALYSIS OF CLEAN WATER DISTRIBUTION IN PDAM OF TIRTA DHARMA PURBALINGGA - Reni Sulistyawati AM; Pingit Broto Atmadi (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2019)
Water has an important role in the lives of human beings and other creatures in nature. None of the life in this world that doesn't need water. Water is a staple for human consumption and has become one of the richesthat are very important. The distribution PDAM of Tirta Dharma Purbalingga, which covers an area of serviceVillage Patemon, Gembong, and Brobot Subdistrict Bojongsari are getting the distribution of water from thereservoir the largest usage volume with Meri in 2018 on November of 31435 m3/month with coverage of a homeConnection as much as 1622 Connection House. Â The research method used was on a needs analysis of the water PDAM: with the calculation of thetheoretical amount of water needs in accordance with the provision of the Director General of Public worksmultiplied by number of customers, while on the analysis of the distribution network: with a pipe calculate theenergy loss, great water pressure, and define the genre. research data used are secondary data obtained fromPDAM Tirta Dharma Purbalingga. Of the process in the get a splitter so the water needs in the service area of the installation of theBojongsari Township includes the village of Patemon, Gembong, and Brobot highest occurred in December of1056900 l/day and kind of flow on the pipeline No. 1 is turbulent flow of 18380.54, so that's not the case brokethe pipe can be done by dividing the 2 pipes so that the flow on the pipeline no 1 can be divided. Types of flow inthe pipeline no 17 and 32 laminar flow that is not going to be precipitation increase discharge pipe at no. 17 and32 in order to increase the speed of the flowmistakes.Key words : clean water,distribution, pipe network.ABSTRAK Air mempunyai peranan penting dalam kehidupan manusia dan makhluk lainnya di alam ini. Tidak adasatupun kehidupan di dunia ini yang tidak membutuhkan air. Air merupakan hal pokok bagi konsumsimanusia dan telah menjadi salah satu kekayaan yang sangat penting. Distribusi PDAM Tirta DharmaPurbalingga yang meliputi wilayah pelayanan Desa Patemon, Gembong, dan Brobot Kecamatan Bojongsari yangmendapatkan distribusi air dari reservoir Meri dengan volume pemakaian terbesar pada tahun 2018 yakni pada bulanNovember sebesar 31435 m3/bulan dengan cakupan Sambungan Rumah sebanyak 1622 Sambungan Rumah.Metode penelitian yang digunakan adalah pada analisa kebutuhan air PDAM yakni dengan perhitungan secara teoritis jumlah kebutuhan air sesuai dengan ketentuan Direktorat Jendran Pekerjaan Umum dikalikandengan jumlah pelanggan, sedangkan pada analisa pipa jaringan distribusi yakni dengan menghitung besarkehilangan energi, tekanan air, dan menentukan jenis aliran. data penelitian yang digunakan adalah datasekunder yang di dapatkan dari PDAM Tirta Dharma Purbalingga. Â Dari proses tersebut di dapatkan Kebutuhan air yang ter jadi pada pelayanan wilayah Instalasi KotaKecamatan Bojongsari yang meliputi Desa Patemon, Gembong, dan Brobot tertinggi terjadi di bulan desembersebesar 1056900 l/hari dan Jenis aliran pada pipa no 1 yaitu aliran turbulen sebesar 18380,54, agar tidak terjadipecah pipa bisa dilakukan dengan membagi 2 pipa sehinggaÂ aliran pada pipa no 1 bisa terbagi. Jenis aliran padapipa no 17 dan 32 yaitu aliran laminer agar tidak terjadi pengendapan bisa dengan menambah debit di pipa no 17dan 32 supaya bisa meningkatkan kecepatan aliran. Kata kunci: Air bersih, distribusi, jaringan pipa.